1976
DOI: 10.1172/jci108316
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of cells on a discontinuous Ficoll gradient. Study of subpopulations of human T cells using anti-T-cell antibodies from patients with systemic lupus erythematosus.

Abstract: A B S T R A C T Patients with active systemic lupus erythematosus (SLE) had a decrease in a subpopulation of cells (fraction D) when peripheral blood lymphocytes were separated on a discontinuous Ficoll gradient. Preincubation of SLE cells at 370C for 30 min led to a marked decrease in this fraction, composed primarily of thymus-derived (T) cells. Supernates of such preincubations were found to cause a reduction in fraction D cells from normal humans. The active factor in the supernate was found to be an IgG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Several studies have emphasized the importance of anti-T cell antibodies in altering T cell number and function in patients with active SLE (7,8,(28)(29)(30)(31)(32)(33)(34). In this regard, recent studies demonstrated that anti-T cell antibodies found in the sera of active SLE patients were selectively reactive with the T5+/T8+ suppressor T cell population (8) and patients with active SLE had decreased numbers of T5+/T8+ subsets (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have emphasized the importance of anti-T cell antibodies in altering T cell number and function in patients with active SLE (7,8,(28)(29)(30)(31)(32)(33)(34). In this regard, recent studies demonstrated that anti-T cell antibodies found in the sera of active SLE patients were selectively reactive with the T5+/T8+ suppressor T cell population (8) and patients with active SLE had decreased numbers of T5+/T8+ subsets (19).…”
Section: Discussionmentioning
confidence: 99%
“…An additional defect in Tnony cells, perhaps induced by anti-T cell antibodies (25)(26)(27)(28)(29)(30), may further impair T cell control mechanisms, thereby allowing uncontrolled B cell hyperactivity. The failure of B cells from such active SLE patients to stimulate in the autologous MLR may be a related inability of activated B cells to stimulate autologous T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrable abnormalities in CMI are more prominent during periods of active disease, with partial or complete resolution during remission (6,7). Considerable indirect evidence suggests that autoantibodies directed toward lymphocyte surface determinants may be of fundamental importance in this regard (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The present consensus is that there is no intrinsic defect in the lymphocytes per se, although this issue is controversial and by no means resolved.…”
Section: Role Of Anti-lymphocyte Antibodies In Abnormal Immune Systemmentioning
confidence: 99%